Life at all costs: European precautionary policies on xenotransplantation. (27th March 2009) - Karlsen, Jan Reinert; Strand, Roger; Solbakk, Jan Helge
Xenotransplantation is becoming an independent political and regulatory issue. Most national regulations and international recommendations prescribe a precautionary approach, including strict monitoring and surveillance of patients. This is due to the risk of xenosis, a disease induced by non-human biological material. The paper shows how the precautionary approach violates fundamental principles of medical ethics, and might violate human rights and European values. Accordingly, the important question is whether to allow xenotransplantation at all, given the risk of xenosis. Indeed, if the precautionary approach recommended by the Council of Europe is implemented, the concept of 'inclusive governance' becomes at best unclear and at worst contradictory and unviable. Can there be an inclusive governance process that democratically leads to an ethical state of exception becoming routine?